2014
DOI: 10.1074/jbc.m114.590034
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Biology Analysis of Apoptosome Formation and Apoptosis Execution Supports Allosteric Procaspase-9 Activation

Abstract: Background: Mathematical simulations of apoptosome formation and mechanisms of caspase-9 activation were conducted and validated against experimental data. Results: Only simulations that assume allosteric caspase-9 activation can accurately reproduce all experimental data. Conclusion: A mechanism of allosteric caspase-9 activation is favored over homodimerization-based activation. Significance: Our findings challenge the dogma that all initiator caspases are activated by homodimerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…6c). To this end, several studies have shown that activation of Caspase-8 as well as that of Caspase-9 and Apaf-1 (via formation of the apoptosome) can lead to the activation of Caspase-3 which is an established mechanism for the execution of apoptosis [50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…6c). To this end, several studies have shown that activation of Caspase-8 as well as that of Caspase-9 and Apaf-1 (via formation of the apoptosome) can lead to the activation of Caspase-3 which is an established mechanism for the execution of apoptosis [50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…In general, death-inducing signaling complexes have been identified as activators of caspase-8 [33, 34], while apoptosomes provide the activation platform for initiation of caspase-9 [29, 35]. A recent study [36] revealed that caspase-9 was activated allosterically by binding to apoptosomes, in which a platform was assembled in response to mitochondria-dependent apoptosis under the influence of XIAP. In the inflammatory response, spinal cord injury activates inflammasomes containing ASC and leads to the cleavage of XIAP [37].…”
Section: Discussionmentioning
confidence: 99%
“…After a death‐inducing signaling, caspases are activated by proteolytic cleavage in a coordinated manner that involves a cascade of cellular elements (McIlwain et al, ; Man and Kanneganti, ). Furthermore, apoptotic signaling pathways are able to modulate the mitochondrial membrane permeability, resulting in a non‐selective opening of the inner membrane pores, loss of mitochondrial transmembrane potential (Δψ), and release of cytochrome c into the cytosol (Ooi and Ma, ) in a multiprotein complex named apoptosome (Würstle and Rehm, ), which is able to induce apoptosis (Guicciardi et al, ). In addition, multiple elements contribute to the processes of apoptosis such as the Bcl‐2 family of proteins, divided into anti‐apoptotic proteins (Bcl‐2, Bcl‐xL, Bcl‐x, Bcl‐XL, Bcl‐XS, Bcl‐w, and BAG) and pro‐apoptotic proteins (Bax, Bak, BH3, Bid, Bad, Bim, Bik, and Blk) (Letai et al, ).…”
Section: Cellular Apoptosis and Its Correlation With Hepatic Fibrosismentioning
confidence: 99%